Fluorescence-based directed termination PCR: direct mutation characterization without sequencing - Chen, Junjian Z. (Oxford University Press, 2001)
We describe a fluorescence-based directed termination PCR (fluorescent DT–PCR) that allows accurate determination of actual sequence changes without dideoxy DNA sequencing. This is achieved using near infrared dye-labeled primers and performing two PCR reactions under low and unbalanced dNTP concentrations. Visualization of resulting termination fragments is accomplished with a dual dye Li-cor DNA sequencer. As each DT–PCR reaction generates two sets of terminating fragments, a pair of complementary reactions with limiting dATP and dCTP collectively provide information on the entire sequence of a target DNA, allowing an accurate determination of any base change. Blind analysis of 78 mutants of the supF reporter gene using fluorescent DT–PCR not only correctly determined the nature and position of all types of substitution mutations in the supF gene, but also allowed rapid scanning of the signature sequences among identical mutations. The method provides simplicity in the generation of terminating fragments and 100% accuracy in mutation characterization. Fluorescent DT–PCR was successfully used to generate a UV-induced spectrum of mutations in the supF gene following replication on a single plate of human DNA repair-deficient cells. We anticipate that the automated DT–PCR method will serve as a cost-effective alternative to dideoxy sequencing in studies involving large-scale analysis for nucleotide sequence changes.